2018
DOI: 10.1038/s41390-018-0158-x
|View full text |Cite
|
Sign up to set email alerts
|

Early body composition changes are associated with neurodevelopmental and metabolic outcomes at 4 years of age in very preterm infants

Abstract: In VPT infants, early FFM gains are associated with faster SOP, whereas post-discharge FM gains are associated with higher BPs at 4 yrs. This shows birth to 4 mos CGA is a sensitive period for growth and its relation to neurodevelopmental and metabolic outcomes. Close monitoring and early nutritional adjustments to optimize quality of gains may improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 38 publications
4
52
1
Order By: Relevance
“…The current analysis extends previous findings by confirming that the relationships between higher amounts of FFM and higher standardized test scores persist out to 24 months of age. However, the current study differed from some of the previous studies in that gains in FFM after term were no longer associated with neurodevelopmental outcomes [1,3,4], suggesting a potentially smaller window of time to intervene with regards to optimizing FFM gains with the goal of improving later neurodevelopment.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…The current analysis extends previous findings by confirming that the relationships between higher amounts of FFM and higher standardized test scores persist out to 24 months of age. However, the current study differed from some of the previous studies in that gains in FFM after term were no longer associated with neurodevelopmental outcomes [1,3,4], suggesting a potentially smaller window of time to intervene with regards to optimizing FFM gains with the goal of improving later neurodevelopment.…”
Section: Discussioncontrasting
confidence: 95%
“…Our study also confirmed the findings of several other studies related to the positive relationship between FFM gains during hospitalization and long-term neurodevelopment. These previous studies also found that gains in FFM, but not FM, prior to hospital discharge, during a time of rapid brain growth and development, were associated with faster speed of brain processing in infancy and at preschool age [1,4], higher standardized test scores at 12 months of age [2], higher scores on the ages and stages questionnaire at two years of age [22] and larger brain volumes [5]. The current analysis extends previous findings by confirming that the relationships between higher amounts of FFM and higher standardized test scores persist out to 24 months of age.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Improved early growth is associated with improved neurodevelopmental outcomes amongst preterm infants [15][16][17]. Specifically, improved fatfree mass (FFM) gains in children born prematurely have been associated with improved neurodevelopment at 12 months of age and faster speed of processing at 4 months and 4 years of age [18][19][20]. To our knowledge, no published study has reported associations between body composition and neurodevelopmental outcomes in children with CGIAs.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have also associated low birth weight with high SBP in children, adolescents and adults Shiell, 1996, Nilsson et al, 1997). A recent study found early FM gains in very preterm infants to be associated with higher blood pressure at 4 years of age (Pfister et al, 2018). There is substantial evidence to suggest that accelerated postnatal catch-up growth in childhood is also associated with later increased SBP (Huxley et al, 2000).…”
Section: Blood Pressurementioning
confidence: 99%